Morphological adaptation of Hungarian words from Juraj Habdelić’s Prvi otca našega Adama greh - Tatjana Vukadinović (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2009)
In this paper we presented morphological adaptation of Hungarian words in Kajkavian standard language. The source for our corpus was the work of Juraj Habdelić Prvi otca našega Adama greh. The method of analysis was comparison of word endings between model and replica. Most noun endings were not significantly modified, while smaller group of nouns, all verbs and all adjectives passed through modifications such as adding, substraction and substitution.